Pemberian Inform Consent Pemeriksaan CT-Scan Dengan Media Kontras Dalam Upaya Peningkatan Keselamatan Pasien - Yeni Cahyati; Kus Endah Aryati; Maria Marsia De Oda Conceicao (NERSMID : Jurnal Keperawatan dan Kebidanan, 2020)
Informed consent means consent given by the patient or family after obtaining information from the radiographer or administration. Every medical action always carries a risk on this basis.Inform consent needs to be implemented in accordance with the Decree of the Minister of Health of the Republic of Indonesia Number 1014 / MENKES / SK / IX / 2008 concerning Diagnostic Radiology Service Standards in Health Service Facilities and Regulations of the Minister of Health of the Republic of Indonesia Number 357 / MENKES / PER / V / 2006 concerning Radiographer Registration and Work Permits. Almost all examinations that are potentially hazardous to patients should be done with informed consent, one example of the importance of providing informed consent for CT-scanning using contrast media in an effort to improve patient safety. This type of research is descriptive. The data analysis carried out in this research is descriptive analysis with existing theoretical approaches. The overall results of the study are in accordance with the function of giving informed consent, namely to provide protection to patients as the subject of health service recipients and to encourage radiographers to be careful in examining patients. By providing informed consent before examination to patients, patient safety can be improved.